PENILAIAN KOMPETENSI KETERAMPILAN BERBASIS PORTOFOLIO PADA PEMBELAJARAN PAI DI MASA PANDEMI COVID-19 - Muhammad Nur Hafidz Afif; Afif, Muhammad Nur Hafidz; Maemoenah, Maemoenah (STAI Syubbanul Wathon Magelang, 2022)
The Covid-19 pandemic that hit Indonesia significantly impacted all lines of life, including the world of education, who feel it. Teaching and learning activities are required to be done remotely/online. Of course, this also affects the components of teaching and learning activities, one of which is assessment. Assessment activities usually carried out in the classroom cannot be carried out due to social restrictions, especially when it comes to skills competency assessment, usually done with a practical assessment. This study aims to determine the Portfolio-Based Skills Competency Assessment in PAI Learning during the Covid19 Pandemic at SMA UII Yogyakarta. From this study, it can be concluded that the appropriate assessment used to assess skill competency in PAI learning during this pandemic is a portfolio-based assessment. PAI teachers have carried out this assessment at UII SMA to assess PAI learning in the aspect of skill competence. In its application, the portfoliobased assessment used to assess the competence of PAI learning skills did not find any significant problems.